Population pharmacokinetics of ethambutol in African children: a pooled analysis. (25th April 2022) - Tikiso, Tjokosela; McIlleron, Helen; Abdelwahab, Mahmoud Tareq; Bekker, Adrie; Hesseling, Anneke; Chabala, Chishala; Davies, Geraint; Zar, Heather J; Rabie, Helena; Andrieux-Meyer, Isabelle; Lee, Janice; Wiesner, Lubbe; et al.
Abstract: Objectives: Ethambutol protects against the development of resistance to co-administered drugs in the intensive phase of first-line anti-TB treatment in children. It is especially relevant in settings with a high prevalence of HIV or isoniazid resistance. We describe the population pharmacokinetics of ethambutol in children with TB to guide dosing in this population. Methods: We pooled data from 188 intensively sampled children from the DATiC, DND i and SHINE studies, who received 15–25 mg/kg ethambutol daily according to WHO guidelines. The median (range) age and weight of the cohort were 1.9 (0.3–12.6) years and 9.6 (3.9–34.5) kg, respectively. Children with HIV (HIV+; n  = 103) received ART (lopinavir/ritonavir in 92%). Results: Ethambutol pharmacokinetics were best described by a two-compartment model with first-order elimination and absorption transit compartments. Clearance was estimated to reach 50% of its mature value by 2 months after birth and 99% by 3 years. Typical steady-state apparent clearance in a 10 kg child was 15.9 L/h. In HIV+ children on lopinavir/ritonavir, bioavailability was reduced by 32% [median (IQR) steady-state C max  = 0.882 (0.669–1.28) versus 1.66 (1.21–2.15) mg/L). In young children, bioavailability correlated with age. At birth, bioavailability was 73.1% of that in children 3.16 years or older. Conclusions: To obtain exposure within the 2–6 mg/L recommended range for C max, the current doses must be doubled (or tripled with HIV+ children on lopinavir/ritonavir) for paediatric patients. This raises concerns regarding the potential for ocular toxicity, which would require evaluation.